The bully free classroom : over 100 tips and strategies for teachers K-8 (Minneapolis, MN : Free Spirit, 2005)
1. School violence--United States--Prevention--Handbooks, manuals, etc. 2. Bullying--United States--Prevention--Handbooks, manuals, etc. 3. Classroom management--United States--Handbooks, manuals, etc. 4. Activitiy programs in education--United States--Handbooks, manuals, etc.
Includes bibliographical references and index
Faculty